WHY DO LECTURERS USE FIGURATIVE LANGUAGE IN CLASSROOM? THE CASE OF EFL LECTURERS - Girik Allo, Markus Deli (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
This study aims to reveal the lecturers’ reasons for using figurative language in EFL classrooms. This research is qualitative, using a case study design. The participants of this study were three EFL Lecturers who were selected using purposive sampling techniques. Their names use pseudonyms to keep their identities confidential. The instruments used are observation and interview. The data analysis techniques used in observation instruments are transcription and coding, while for interviews use thematic analysis. The result of this study confirms that the lecturers’ reasons of using figurative language in EFL Classroom are introducing language and culture as feedback to improve students’ understanding of the lessons, to help students understand the lessons, to motivate students in the learning process, to enhance the students’ language style competence, and to train students’ critical thinking. This study is limited to the types and intentions of implementing Figurative Language in context. Therefore, future researchers are recommended to elaborate on the impact of its implementation and model.